Removal and elimination of pharmaceuticals in water using zeolites in diverse adsorption processes and catalytic advanced oxidation technologies—a critical review (2024)
Water pollution by pharmaceuticals is a current worrying environmental problem. Adsorption and catalytic processes using zeolites have been employed in several studies to remove/degrade pharmaceuticals from water. The interest of researchers in these two strategies based on the utilization of zeolites (i.e., adsorption and advanced oxidation technologies, AOT) is continuously growing. Then, this work presents a literature review, considering the origin of the zeolites (natural vs. synthetic) and the modifications of zeolites (e.g., the addition of surfactants) for the adsorption of diverse pharmaceuticals. The role of zeolites in catalytic ozonation, Fenton-based systems, and activation of peroxymonosulfate and peroxydisulfate is detailed. Also, the primary transformations of pharmaceuticals induced by these AOTs were examined. Moreover, the gaps regarding biodegradability and toxicity of the transformation products coming from the degradation of pharmaceuticals by the zeolites-based processes were discussed. To overcome the scarcity of information regarding the biodegradability and toxicity of the primary transformation products observed in the revised works, an initial approach to these topics, using a predictive tool, was made. Finally, from the present review, it was evidenced the need for future works involving zeolites that provide results about the simultaneous removal/elimination of multiple pharmaceuticals in complex matrices (e.g., hospital wastewater or municipal wastewater), new information about biodegradability and toxicity plus the development of combination or coupling of processes with other AOTs (e.g., sonochemistry) or classical systems (e.g., biological process).